Analytical approximations for the self-field distribution of a superconducting tape between iron cores. (1st December 2022) - Hao, Luning; Dong, Fangliang; Yang, Jiabin; Patel, Ismail; Wei, Haigening; Wang, Qi; Hu, Jintao; Tian, Mengyuan; Shah, Adil; Shen, Boyang; Coombs, Tim
Abstract: Magnetic switches apply AC magnetic fields to DC current-carrying high temperature superconducting (HTS) tapes to generate DC voltages and are commonly used in the persistent current switches (PCSs) and flux pumps to charge HTS-coated conductor magnets. Normally, they are made of copper field coils and iron cores with narrow air gaps for the HTS tape to pass through. However, the perpendicular components of the self-field of the HTS tape in the air gap can be enhanced by the iron cores and cause a critical current reduction of up to 40% to the tape. If ignored, this reduction, rather than the magnets themselves, will limit the current carrying capability of the HTS magnets. To tackle this problem, we present analytical approximations to calculate the self-field distribution of a superconducting tape between iron cores. The approximate solutions are based on the method of images in electromagnetics to simplify the derivation and are then verified by the experiments and 3D finite element method models using the T–A formulation. The solutions are universal and can be applied to almost all the magnetic switches currently in use. A case study of typical magnetic switches shows that the solutions can be used to determine the critical current reduction quickly and accurately, analyse the influence of different parameters, and simplify the design process of magnetic switches. The results can significantly benefit the design and optimisation of PCSs and flux pumps for HTS magnet charging systems in the future.